Diagnóstico dos resíduos de construção e demolição: uma contribuição à elaboração e implantação da gestão integrada dos RCD no município de Guaratinguetá – SP - Mattos, Thomaz Lourenço de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The problem of solid waste has caused discussions about the huge amount that is generated in Brazilian cities, in particular the waste from construction and demolition (CDW), called spoil. In many cases these wastes are disposed of improperly and even criminally in urban areas, causing serious economic, social and environmental problems. Due to the lack of public policies and appropriate management of such waste came up with the CONAMA, in its resolution nº 307 of 2002, the obligation of municipalities in deploy the integrated management of construction and demolition wastes for the resolution of problems caused by inadequate management and disposal of such waste. By following a methodology suggested by Pinto & González (2005), with adaptations of other authors, it is proposed in this work the lifting of a diagnosis of the CDW in the municipality of Guaratinguetá-SP, through theoretical analysis and field research, with purpose to guide the public servants in the elaboration and implementation of integrated management. The results must contain information necessary for that end, such as the knowledge of generators, agents, collectors and transporters, disposition areas and the disposal of waste

A problemática dos resíduos sólidos tem causado discussões a respeito da enorme quantidade que é gerada nas cidades brasileiras, em especial os resíduos provenientes de construção e demolição (RCD), denominado entulho. Em muitos casos esses resíduos são descartados de maneira imprópria e até criminosa nas áreas urbanas, causando graves problemas ambientais, sociais e econômicos. Devido à falta de políticas públicas e gerenciamento adequado desses resíduos surgiu com o CONAMA, na sua resolução nº 307 de 2002, a obrigatoriedade dos municípios brasileiros em implantar a Gestão Integrada de Resíduos de Construção e Demolição para a resolução dos problemas gerados pelo manejo e disposição inadequados desses resíduos. Seguindo uma metodologia sugerida por Pinto & González (2005), com adaptações de outros autores, propõe-se nesse trabalho o levantamento de um diagnóstico dos RCD no município de Guaratinguetá – SP, através de análises teóricas e pesquisa de campo, com a finalidade de nortear os agentes públicos na elaboração e implantação da Gestão Integrada. Os resultados devem conter informações necessárias a esse fim, tais como o conhecimento dos agentes geradores, agentes coletores e transportadores, as áreas de descarte e disposição dos resíduos
Keywords: Industria de construção civil – Eliminação de residuos; Demolição – Resíduos sólidos; Liteira (Entulho); Civil construction